Diazinon toxicity in hepatic and spleen mononuclear cells is associated to early induction of oxidative stress. Issue 10 (3rd October 2022) - Girón-Pérez, Manuel Iván; Mary, Verónica S.; Rubinstein, Héctor R.; Toledo-Ibarra, Gladys A.; Theumer, Martín G.
ABSTRACT: Diazinon is an organophosphorus pesticide, which may have potential toxic effects on the liver and immune system; however, the underlying mechanisms remain mostly unidentified. This work is aimed at evaluating the oxidative stress and cell cycle alterations elicited by low-dose diazinon in a rat liver cell line (BRL-3A) and spleen mononuclear cells (SMC) from Wistar rats. Diazinon (10–50 μM) caused early reactive oxygen species (ROS) generation (from 4 h) as well as increased O2 - level (from 0.5 h), which led to subsequent lipid peroxidation at 24 h, in BRL-3A cells. In SMC, diazinon (20 μM) produced similar increases in ROS levels, at 4 and 24 h, with the highest O2 - level being found at 4 h. Low-dose diazinon induced G1-phase arrest and cell death in hepatic cells and SMC. Therefore, diazinon could affect the liver and the immunological system through the premature oxidative stress induction. Abbreviations: O2 - : superoxide anion radical; ROS: reactive oxygen species; SMC: spleen mononuclear cells; TBARS: thiobarbituric acid reactive substances